Synthesis of Catechol Thioethers through Gallic Acid/Fe2(SO4)3 Catalyzed Aerobic Oxidative Coupling of Thiols and Catechol Derivatives. Issue 48 (22nd December 2021) - Si, Mengyuan; Liu, Zhongyuan; Dou, Yingchao; Yang, Guanyu
Abstract: A newly developed cooperative catalytic system Galic acid/Fe2 (SO4 )3 was employed in the syntheses of catechol thioethers through the direct aerobic oxidative coupling of various thiols with catechol derivatives. As the first organocatalytic oxidative method to prepare catechol thioethers except the enzymatical cases, it exhibits good tolerance and selectivity, leading to the good products in up to 95 % yields. It was postulated to undergo the divergent Michael‐type nucleophilic conjugate addition (1, 4‐type or 1, 6‐type) of the thiols onto the in‐situ generated ortho ‐benzoquinones. Abstract : The syntheses of catechol thioethers were realized with a catalytic aerobic oxidative protocol of a newly developed cooperative catalytic system gallic acid/Fe2 (SO4 )3 . The divergent Michael‐type nucleophilic addition of thiols onto the in‐situ generated ortho ‐benzoquinones was believed to be involved.